Peran Media Sosial Dalam Proses Demokrasi: Analisis Peran Dan Dampak Media Sosial Dalam Kegiatan Kampanye Pemilu Presiden Tahun 2019 - nurcahyani, nabila; Nurhaliza, Salma Triana; Febriyanti, Aisyah; Lukman, Fiman (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Pasundan Bandung, 2023)
With the 2019 elections, social media has emerged as a highly effective tool for shaping public perceptions and attitudes towards both competitors. But it is important to remember that social media also has negative effects. Most social media users usually only see content that supports their own opinions. Moreover, the ability of voters to make informed decisions is hampered by the spread of chaos and misleading information, which is a significant problem. The aim of this research is to determine the influence and function of social media in the campaign process. Qualitative research emphasizes interpretation and understanding of social contexts, while secondary data is used to detail existing data from various sources, such as journals, websites, and photos relevant to research topics. The data collection technique chosen is documentation, with data analysis involving drawing conclusions from collected data. Keywords: Democracy, Campaigns, Social Media